Pengaruh Penerapan Good Corporate Governance Terhadap Kinerja Perusahaan Yang Terdaftar Di Bursa Efek Indonesia - - Melvina; Mitha Dwi Restuti (Conference In Business, Accounting, And Management (CBAM), 2012)
Good corporate governance enable company to increase their performance through effective and efficient operation. The purpose of this research were investigate the effect of good corporate governance to company performance. Sample of this research is 66 listed company and had Corporate Governance Perception Index (CGPI). Company performance measured by ROE and Tobin’s Q. Multiple regression used to test the hypotheses. The result were good corporate governance had no effect on ROE and Tobin’s Q. This result indicate that good corporate governance did not have effect on short term and the effect can be seen in the long term.Keywords: good corporate governance, company performance